Korelasi Dukungan Orang Tua, Motivasi, dan Kepercayaan Diri Atlet di Klub Renang Flam Aquatic Kediri - Adji Adyanto; Anindya Mar'atus Sholikhah; Joesoef Roepajadi; Anna Noordia (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyse the correlations between parental support, motivation, and self-confidence. The research design used was quantitative research, and the method used was a survey with a Likert scale. The population was all athletes at the Flam Aquatic Kediri swimming club. The sampling technique used was saturated sampling, and this research used 37 athletes as the sample. The instrument was analysed by Pearson's product-moment and Bivariate correlation analysis test. The result shows that F count = 8.621 < F table = 3.28, a significant value of 0.001 < a significant level of 0.05, and the R-squared value was 0.336 which means that there is a significant correlation between the variables of parental support, motivation, and self-confidence of athletes at the Flam Aquatic Kediri swimming club. It correlates with 33.6%. It can be concluded that this research hypothesis,